2017
DOI: 10.2298/vsp141118141j
|View full text |Cite
|
Sign up to set email alerts
|

Silent sinus syndrome: One more reason for an ophthalmologist to have a rhinologist as a good friend

Abstract: nema

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…[12,18] Given the rarity of SSS and the very high prevalence of obstruction of the maxillary sinus ostium, this theory has come under question. [3] Several authors have demonstrated absolute normality of the maxillary sinus walls before clinical and radiological manifestations of SSS, which confirms that it is an acquired condition. [1,6,12] In this enclosed cavity, subsequent gas resorption leads to sub-atmospheric pressure that creates a vacuum, thus creating a suction effect of negative pressure within the maxillary sinus; this vacuum may induce osteopenia, bone remodeling, and retraction of the sinus walls, similar to retraction in the middle ear caused by Eustachian tube dysfunction.…”
Section: Pathophysiologymentioning
confidence: 79%
See 4 more Smart Citations
“…[12,18] Given the rarity of SSS and the very high prevalence of obstruction of the maxillary sinus ostium, this theory has come under question. [3] Several authors have demonstrated absolute normality of the maxillary sinus walls before clinical and radiological manifestations of SSS, which confirms that it is an acquired condition. [1,6,12] In this enclosed cavity, subsequent gas resorption leads to sub-atmospheric pressure that creates a vacuum, thus creating a suction effect of negative pressure within the maxillary sinus; this vacuum may induce osteopenia, bone remodeling, and retraction of the sinus walls, similar to retraction in the middle ear caused by Eustachian tube dysfunction.…”
Section: Pathophysiologymentioning
confidence: 79%
“…e first theory is a progressive development of a small sinus with chronic obstructive sinusitis as an initial cause. [3] Davidson et al [12] and Kass et al [13] have documented negative maxillary sinus pressure in patients with clinical and radiographic characteristics of SSS, supporting the theory of negative maxillary sinus pressure leading to SSS.…”
Section: Pathophysiologymentioning
confidence: 91%
See 3 more Smart Citations